(untitled) (SASI, 2016)
In today’s borderless business era, arbitration is a very popular dispute settlement institution used by businesses. However, it is not uncommon for business people, especially those who win cases, to be frustrated when faced with the implementation of arbitration rulings involving the courts. The process of dispute resolution at the National Arbitration Institute, as it is commonly known in the Court, dispute resolution will lead to a decision (National Arbitration Award). Article 70 of Law no. 30 of 1999 on Arbitration and Alternative Dispute Settlement, affirming that the arbitral award can only be canceled if it is suspected to contain elements of fake Letter / Document, or found documents hidden by the opponent or a judgment taken from the guile by one of the parties in Examination, but the fact in practice the court still receives the request and cancels the arbitration decision outside the context of that article which is the basis of the reference for the cancellation of the arbitral award.